Variasi Diameter Intake Manifold dan Throttle Body terhadap Performa Mesin 155 CC: Variation of Intake Manifold and Throttle Body Diameter on 155 CC Engine Performance - I Putu Wahyu Widi Astika; Ida Bagus Putu Purwadnyana; Kadek Rihendra Dantes (Universitas Pendidikan Ganesha, 2026)
This study aimed to analyze the effect of intake manifold and throttle body diameter variations on engine performance and fuel consumption of a 2019 Yamaha NMAX 155 cc motorcycle using Pertamax 98 fuel. The diameter variations tested consisted of the standard 28 mm, a modified 30 mm, and a modified 32 mm. A quantitative experimental method was employed, with torque and power measured using a dynamometer, while fuel consumption was determined using the volumetric method. Testing was conducted within an engine speed range of 3,000–6,000 rpm. The results showed that variations in intake manifold and throttle body diameters significantly affected engine performance and fuel consumption characteristics. The 32 mm diameter produced the highest performance, achieving a maximum torque of 21.88 Nm at 3,500 rpm and a maximum power output of 11.5 HP at 4,500 rpm. However, this configuration also resulted in the highest fuel consumption, reaching 0.661 kg/h at 6,000 rpm. Meanwhile, the 30 mm diameter provided a balanced improvement in performance while maintaining relatively good fuel efficiency. The use of Pertamax 98 supported a more optimal combustion process and helped reduce engine knocking.